Stock market contagion in Central and Eastern Europe: unexpected volatility and extreme co-exceedance*. Issue 5 (24th March 2018) - Horváth, Roman; Lyócsa, Štefan; Baumöhl, Eduard
Abstract: We examine whether there is contagion from the US stock market to six Central and Eastern European stock markets. We use a novel measure of contagion that examines whether volatility shocks in the US stock market coupled with negative returns are followed by higher co-exceedance between US and emerging stock markets. Using our approach and controlling for a set of market-related variables, we show that during the period from 1998 to 2014, financial contagion occurred, that is, unexpected negative events in the US market are followed by higher co-exceedance between US and Central and Eastern European stock markets. Even though contagion is stronger during the financial crisis, it also occurs in tranquil times.